Efektifitas Jus Semangka Dan Jus Pepaya Terhadap Penurunan Tekanan Darah Penderita Hipertensi Di Puskesmas Kembaran 1 Banyumas - Cahyani, Tri Oka Regita; Mujahid, Ikhsan (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: Â To determine the effectiveness of watermelon juice and papaya juice on blood pressure in patients with hypertension at the Puskesmas (Public Health Care Center) Kembaran I Banyumas.Methods: This research uses quantitative methods with a quasi-experimental design with a pre-post group. The sample selection using a purposive sampling technique obtained 15 respondents in the watermelon juice group and 15 respondents in the papaya juice group. The statistical tests used are Paired t-test and independent t-testResults: The results of the study found that the average systolic blood pressure of the watermelon juice group was from 148.13 in the beginning to 138.93. The average diastolic blood pressure was 85.80 to 80.60. While the average systolic blood pressure of the papaya juice group was from 149.40 in the beginning to 145.67, the average diastolic blood pressure was from 84.20 to 80.80. There were significant differences in systolic and diastolic blood pressure before and after treatment in the watermelon juice and papaya juice groups with p0.05. There is a significant difference in the effectiveness of watermelon juice and papaya juice on the reduction of systolic and diastolic blood pressure with p0.05.Conclusion: Watermelon juice is more effective than papaya juice for reducing blood pressure in patients with hypertension at the Puskesmas Kembaran 1 Banyumas.